Solid lipid nanoparticles and nanostructured lipid carrier-based nanotherapeutics in treatment of psoriasis: a comparative study. (1st February 2017) - Arora, Rhythm; Katiyar, Sameer S.; Kushwah, Varun; Jain, Sanyog
ABSTRACT: Background : The present work focuses on the development of ultra-small solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) encapsulating cyclosporine and calcipotriol, further incorporated into gel, increasing their penetration through the skin. Research design and methods : Developed SLN and NLC were characterized regarding particle size, zeta potential, %entrapment efficiency and dispersed into carbopol 934P-NF gel. Gel was further characterized for rheological behavior and spreadability. Ex vivo dermatokinetic by tape stripping method, in vitro efficacy on HaCaT cell lines and in vivo efficacy on imiquimod induced psoriatic model in mice were evaluated. Results : Ultra-small (size<100 nm) particles were formed with high entrapment efficiency and spherical morphology. Ex vivo dermatokinetic studies revealed deeper and confined drug penetration of lipid formulation gel in epidermal layers as compared to free drug. In vitro study on HaCaT cell lines depicted higher uptake and high efficacy owing to decrease in cell viability for NLC. The anti-psoriatic efficacy in BALB/c mice (evaluated on basis of cytokine levels and skin morphology) highlighted potential of drug-loaded NLC significantly higher as compared to drug loaded SLN and marketed formulation Betagel. Conclusions : The study demonstrated that NLC gel had higher efficacy in psoriatic management and hold promise for further exploration.